Film dosimetry using a smart device camera: a feasibility study for point dose measurements. (3rd October 2017) - Aland, Trent; Jhala, Ekta; Kairn, Tanya; Trapp, Jamie
Abstract: In this work, a methodology for using a smartphone camera, in conjunction with a light-tight box operating in reflective transmission mode, is investigated as a proof of concept for use as a film dosimetry system. An imaging system was designed to allow the camera of a smartphone to be used as a pseudo densitometer. Ten pieces of Gafchromic EBT3 film were irradiated to doses up to 16.89 Gy and used to evaluate the effects of reproducibility and orientation, as well as the ability to create an accurate dose response curve for the smartphone based dosimetry system, using all three colour channels. Results were compared to a flatbed scanner system. Overall uncertainty was found to be best for the red channel with an uncertainty of 2.4% identified for film irradiated to 2.5 Gy and digitised using the smartphone system. This proof of concept exercise showed that although uncertainties still exceed a flatbed scanner system, the smartphone system may be useful for providing point dose measurements in situations where conventional flatbed scanners (or other dosimetry systems) are unavailable or unaffordable.